Emil PODRUG, Toni BRAJKOVIĆ, Željko KRNČEVIĆ, Arheološki tragovi kultova i religija na šibenskom području (Archaeological Traces of Cults and Religions in the Šibenik Area), Muzej grada Šibenika, 2008, p. 263, ISBN 978-953-6844-17-3 - Zeman, Maja (2009)
The publication Archaeological Traces of Cults and Religions in the Šibenik Area (published in 2008) deals primarily with those monuments that most adequately present the complexity of transitions of different cults and religious beliefs from Prehistory to the Middle Ages in the Šibenik area. Thus in the first part of the book the most important archaeological sites and monuments – discovered on the localities in Danilo, Bribir, Skradin, district of Vodice, Donje polje near Šibenik etc. - are presented in social and cultural context, with special interest given to the emergence and spreading of certain beliefs and rituals and their influence on everyday life. The book ends with a summary in English and a complete Catalogue of finds and monuments that were presented at the exhibition, consisting of 179 catalogue units.
Projekt MZOS
ENG